The Fundamental Difference Hypothesis: Expanding the Conversation in Language Learning Motivation - Al-Hoorie, Ali H.; Hiver, Phil (SAGE open, 2020)
In this study, we examine the fundamental difference hypothesis in language motivation, which suggests that language learning—at the motivational level—is qualitatively different from learning other school subjects. Despite being a long-standing assumption, few investigations have directly examined it. Using a comparative cross-sectional approach, we adapted the L2 Motivational Self System and collected data from South Korean high school students (N = 644) related to their motivation to learn English (L2), Chinese (L3), and mathematics (a nonlanguage subject). Contrary to the fundamental difference hypothesis, the L2 Motivational Self System fit these three subjects well and did not reveal clear uniqueness pointing toward a qualitative difference in favor of language learning motivation. We use these findings to discuss the possibility of a more global and parsimonious learning motivation theory to accommodate multiple languages in addition to nonlanguage subjects. We also discuss the need for language learning researchers to reengage with other learning sciences.